Variation in defence strategies in the metal hyperaccumulator plant Noccaea caerulescens is indicative of synergies and trade-offs between forms of defence - Helen N. Fones; Gail M. Preston; J. Andrew C. Smith (Royal Society Open Science, 2019)
In the metal hyperaccumulator plant Noccaea caerulescens, zinc may provide a defence against pathogens. However, zinc accumulation is a variable trait in this species. We hypothesize that this variability affects the outcome of interactions between metal accumulation and the various constitutive and inducible defences that N. caerulescens shares with non-accumulator plants. We compare zinc concentrations, glucosinolate concentrations and inducible stress responses, including reactive oxygen species (ROS) and cell death, in four N. caerulescens populations, and relate these to the growth of the plant pathogen Pseudomonas syringae, its zinc tolerance mutants and Pseudomonas pathogens isolated from a natural population of N. caerulescens. The populations display strikingly different combinations of defences. Where defences are successful, pathogens are limited primarily by metals, cell death or organic defences; there is evidence of population-dependent trade-offs or synergies between these. In addition, we find evidence that Pseudomonas pathogens have the capacity to overcome any of these defences, indicating that the arms race continues. These data indicate that defensive enhancement, joint effects and trade-offs between different forms of defence are all plausible explanations for the variation we observe between populations, with factors including metal availability and metal-tolerant pathogen load probably shaping the response of each population to infection.